2005
DOI: 10.1111/j.1651-2227.2005.tb02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile of recombinant human N‐acetylgalactosamine 4‐sulphatase enzyme replacement therapy in patients with mucopolysaccharidosis VI (Maroteaux–Lamy syndrome): a phase I/II study

Abstract: Aim: Mucopolysaccharidosis VI (Maroteaux–Lamy syndrome) is a lysosomal storage disease caused by a deficiency of the enzyme N‐acetylgalactosamine 4‐sulphatase (ASB). Enzyme replacement therapy with recombinant human ASB (rhASB) has been studied in a randomized, double‐blind, two‐dose (0.2 and 1.0 mg/kg/week) phase I/II study (n=7) followed by an open‐label single dose (1.0 mg/kg/week) extension study. We report the pharmacokinetic profile of rhASB and the impact of antibody development. Methods: Pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 11 publications
3
35
0
1
Order By: Relevance
“…Although visceromegaly in MPS VI is not as prominent as other types of MPS, the five (50%) patients with hepatomegaly in the 48-week open-label phase II trial demonstrated reduction in liver size, with four demonstrating normal age-weight adjusted liver size. 298 In the same study, the three patients with the most severe abnormalities in nocturnal pulse oximetry experienced improvement in average oxygen saturation and decrease in time spent below 90% saturation. In the 24-week phase III doubleblind, randomized, placebo-controlled study, the rhASB group demonstrated a significant improvement in the 12-minute walk test distance compared with the placebo group.…”
Section: Therapymentioning
confidence: 85%
See 1 more Smart Citation
“…Although visceromegaly in MPS VI is not as prominent as other types of MPS, the five (50%) patients with hepatomegaly in the 48-week open-label phase II trial demonstrated reduction in liver size, with four demonstrating normal age-weight adjusted liver size. 298 In the same study, the three patients with the most severe abnormalities in nocturnal pulse oximetry experienced improvement in average oxygen saturation and decrease in time spent below 90% saturation. In the 24-week phase III doubleblind, randomized, placebo-controlled study, the rhASB group demonstrated a significant improvement in the 12-minute walk test distance compared with the placebo group.…”
Section: Therapymentioning
confidence: 85%
“…Results of clinical trials for recombinant human arylsulfatase B (rhASB, Naglazyme; Biomarin Corporation, Novato, CA) have been published. [297][298][299] The 1 mg/kg/week dose produced a greater reduction in urinary GAG excretion compared with the 0.2 mg/kg/week dose. Although visceromegaly in MPS VI is not as prominent as other types of MPS, the five (50%) patients with hepatomegaly in the 48-week open-label phase II trial demonstrated reduction in liver size, with four demonstrating normal age-weight adjusted liver size.…”
Section: Therapymentioning
confidence: 99%
“…ERT became a reality approved for clinical use in 2003 for MPS I, in 2005 for MPS VI, and in 2006 for MPS II (Kakkis et al , 2001a,b; Wraith et al , 2004, 2007; Harmatz et al , 2005a,b, 2008; Wraith, 2005; Muenzer et al , 2006, 2007; Sifuentes et al , 2007; Clarke, 2008; Clarke et al , 2009; Giugliani et al , 2009). …”
Section: Treatmentmentioning
confidence: 99%
“…Phase I/II - The study by Harmatz et al (2005b) was performed in six patients, using two different doses of the drug, 1 mg/kg and 0.2 mg/kg, given in weekly infusions during 48 weeks.…”
Section: Treatmentmentioning
confidence: 99%
“…International management guidelines for MPS VI recommend galsulfase ERT as the first-line therapy for treating MPS VI patients [Giugliani et al, 2007]. Three clinical trials, including a randomized double-blind placebo-controlled Phase 3 trial, showed improved endurance based on increased 12-minute walk test (12MWT) and 3-minute stair-climb (3MSC) measurements, and decreased urinary GAGs, demonstrating efficacy of galsulfase in the MPS VI patients [Harmatz et al, 2006; Harmatz et al, 2005a; Harmatz et al, 2005b; Harmatz et al, 2004]. An analysis of pooled data from the clinical trial program showed improvement in pulmonary function tests and growth velocity in patients (n=56, mean age approximately 12 years, range 5 to 29 years) who received ERT for up to 240 weeks [Decker et al, 2010; Harmatz et al, 2010].…”
Section: Introductionmentioning
confidence: 99%